Lack of an Association between Neutrophil-to-Lymphocyte Ratio and PSA Failure of Prostate Cancer Patients Who Underwent Radical Prostatectomy. (20th April 2016) - Maeda, Yoko; Kawahara, Takashi; Koizumi, Mitsuyuki; Ito, Hiroki; Kumano, Yohei; Ohtaka, Mari; Kondo, Takuya; Mochizuki, Taku; Hattori, Yusuke; Teranishi, Jun-ichi; Yumura, Yasushi; Miyoshi, Yasuhide; et al.
Abstract : Introduction . The neutrophil-to-lymphocyte ratio (NLR), which can be easily calculated from routine complete blood counts of the peripheral blood, has been suggested to serve as a prognostic factor for some solid malignancies. In the present study, we aimed to determine the relationship between NLR in prostate cancer patients undergoing radical prostatectomy (RP) and their prognosis. Materials and Methods . We assessed NLR in 73 men (patients) who received RP for their prostate cancer. We also performed immunohistochemistry for CD8 and CD66b in a separate set of RP specimens. Results . The median NLR in the 73 patients was 1.85. There were no significant correlations of NLR with tumor grade (p = 0.834 ), pathological T stage (p = 0.082 ), lymph node metastasis (p = 0.062 ), or resection margin status (p = 0.772 ). Based on the area under the receiver operator characteristic curve (AUROC) to predict biochemical recurrence after RP, potential NLR cut-off point was determined to be 2.88 or 3.88. However, both of these cut-off points did not precisely predict the prognosis. There were no statistically significant differences in the number of CD66b-positive neutrophils or CD8-positive lymphocytes between stromal tissues adjacent to cancer glands and stromal tissues away from cancer glands and between different grades or stages of tumors. Conclusions . There was no association between NLR and biochemical failure after prostatectomy.